Comparison of carbohydrate contents and endogenous hormones in sweet cherry flower buds between different altitude areas in Hangzhou - ZHANG Chen; LIU Hui; RUAN Ruoxin; LUO Huifeng; HUANG Kangkang; XI Dujun; PEI Jiabo; SHEN Guozheng (Guoshu xuebao)
[Objective] Sweet cherry (Prunus avium L.) originated in Europe, is the earliest mature deciduous fruit crop in the north of China, famous for "the first spring fruit". With the rapid development of sweet cherry production in the 1990s, its cultivation range and quantity have been greatly expanded. It was reported that sweet cherry could obtain stable and high yield in the high altitude region in southwest China, where it was classified as a suitable planting area for sweet cherry. Now sweet cherry has also become an emerging industry for farmers in high altitude cold region to generate income. It can be seen that the high altitude areas in the south China with similar habitats also have the climatic conditions for successful cultivation of sweet cherries. Flowers are the reproductive organs of plants, the quantity of flower bud development are closely related to the fruit traits and yield at fruiting stage. Carbohydrate is an important material basis for flower bud development. Flower bud differentiation of sweet cherry goes through three stages: physiological initiation, morphological differentiation and flower organ formation, among which flower organ formation occurs in the spring of the following year after winter dormancy. As a typical fruit tree with first flowering and then sprouting leaf, the energy and material required for flower organ development in spring of sweet cherry depend on the accumulation of nutrients within the tree in the previous growing season. Therefore, the study on carbohydrate contents and endogenous hormone levels in the flower bud during dormancy, especially before the flower bud sprouting, has certain guidance for the analysis of flower bud quality and following yield. In this paper, the difference in carbohydrate content and endogenous hormone level in flower buds of sweet cherry between different altitude areas in Hangzhou were compared, in order to reveal the reason for low yield of sweet cherry in low altitude region of Hangzhou at the physiological level. [Methods] Five years old sweet cherry trees grown at high and low altitudes respectively in Hangzhou were used as the experimental materials. Firstly, the defoliation period and budbreak period in two regions were observed for past three years. On this basis, from November 2021 to March 2022, flower buds were collected before dormancy (1 month before complete leaf fall), during dormancy (1 month after complete leaf fall), and before budbreak (when flower buds just emerged red) to determine the relevant physiological indexes. The carbohydrate indices (such as starch content, different sugar component content, soluble protein content and free amino content) and endogenous hormones indices (such as GAs, IAA, ABA and CTKS) were determined at three stages. The flower bud weight was investigated, too. Finally, the content levels of flower buds at different stages were analyzed by principal component analysis. Grey relation analysis (GRA) and GRA-SVM model were used to analyze the correlation degree between flower bud weight and the flower bud inclusion index. [Results] The results revealed that after dormancy, the content of starch and free amino acid in flower buds increased, while the content of soluble protein decreased. Before budbreak, the content of free amino acids in flower buds at high altitude was 1.22 times more than that at low altitude, but there was no significant difference in soluble protein content between two regions. The variation trend of the four sugar components was the same, but the content of individual sugar components varied greatly between two regions. Sucrose and sorbitol are the dominant sugar components in sweet cherry flower buds. Before budbreak, there was no significant difference in sucrose and glucose contents between two regions, but the sorbitol content at high altitude was significantly higher than that at low altitude. The contents of sorbitol, fructose and glucose were 1.21, 1.18 and 1.11 times more than the value at high altitude, respectively. In terms of endogenous hormones, the content of ABA was the highest, followed by IAA, and the content of GAs was the lowest. Among CTKs, iPA content was lower and DHZR content was higher in flower buds in two regions. The content of CTKs and GAs at high altitude was 1.22 and 1.19 times higher than the low altitude value, respectively, while the content of ABA at low altitude was 1.07 times more than the value at high altitude. The CTKs/GAs values in flower buds of two regions were significantly different. The value at the high altitude was still 1.02 times higher than that at the low altitude. There was no significant difference in the weight of single flower bud among the three stages. After dormancy, the weight of single flower bud increased in both regions, and the value at high altitude was slightly higher than that at low altitude. From the appearance observation, it could be seen that the flower bud scales in two regions were tightly wrapped, but the flower bud at high altitude was fuller. Principal component analysis showed that the content level of flower buds at high altitude was lower before dormancy. After the accumulation of dormancy period, the content in flower bud at high altitude was higher than that at low altitude. Before budbreak, the content level at high altitude was still higher than that at the low altitude. GRA analysis showed that the correlation between flower bud inclusions and weight was not same at different stages. The correlation coefficient between the inclusions and the weight of the flower buds was larger before budbreak. After comprehensive analysis of the whole stage data, it could be seen that the top five factors of correlation coefficient with flower bud weight belonged to GAs, starch, glucose and CTKs, respectively. GRA-SVM model also confirmed that there was a certain coefficient correlation between flower bud weight and the selected factors. [Conclusion] The change patterns of flower bud inclusions at different dormancy stages of sweet cherry in two regions were basically the same, but the contents were different. The overall level of flower bud inclusions in high altitude area of Hangzhou was higher than that in low altitude area. Combined with GRA-SVM model, it could be further revealed that the low level of some inclusions was the internal physiological reason for the low flower bud weight of sweet cherry.